”De står som en besætning i et fremmed land.” - Racekrig, besættelse og højrepopulistisk historiepolitik - Christensen, Søren (Slagmark - Tidsskrift for idéhistorie, 2018)
The article discusses one of the ways in which the politics of history is performed by contemporary Western European right-wing populism. This discussion is conducted with reference to Michel Foucault’s analysis of the historical discourse on ’racial war’ of the 17th and 18th centuries. It is argued that, in its most basic features, this discourse is not simply a historically delimited discourse, but a specific form of critique which survives in modified forms within modernity and one of whose contemporary versions is the anti-establishment discourse of right-wing populism. Specifically, the article discusses how the theme of ’occupation’ so central to the discourse on racial war is re-articulated in two instances (Danish and French) of current right-wing populist discourse, not simply with reference to current ’mass immigration’, but also with reference to experiences of occupation during World War II. The article concludes that the age-old theme of occupation is here integrated into a new politics of history which basically concerns the questions of the responsibility for and the heritage from totalitarianism.